Myositis Ossificans of the Pubic Region Presenting as a Rare Variant of Athletic Pubalgia: A Case Report - Thakur, Dr mahipal singh thakur; sachin reja, dr sachin reja (Indian Journal of Case Reports, 2026)
Athletic pubalgia is a frequent cause of chronic groin pain in athletes; however, rare pathological entities may mimicits presentation and delay diagnosis. Myositis ossificans (MO) is a benign, heterotopic ossification disorder typicallyoccurring in large muscle groups following trauma. Pubic region involvement is exceptionally uncommon and mayclinically resemble chronic athletic pubalgia, soft tissue tumors, or osteogenic malignancies. We report a case of a21-year-old female track and field athlete presenting with a 2-year history of progressive pubic pain refractory toconservative management. Over the past 6 months, she developed a hard, progressively enlarging mass extending intothe labia majora, significantly limiting athletic performance and daily activities. Radiological evaluation revealed amature heterotopic ossified mass in the parasymphyseal region, completely separate from the pubic bone. The patientunderwent complete surgical excision through a multidisciplinary approach. Histopathology confirmed mature MOwith a characteristic zonation pattern. Postoperatively, she experienced immediate symptom relief and returned tosport within 2 months. This case highlights an unusual presentation of MO mimicking refractory athletic pubalgia andemphasizes the importance of early imaging and surgical management in selected cases